A simple technique for preservation of female perineal pattern of Meloidogyne spp. (The Journal of Plant Protection Sciences, 2024)
Morphology of female perineal pattern (area  around anus and vulva) of the root knot nema tode (Meloidogyne spp.) is studied to identify  the species under the genus as this was origi nally proposed by Chitwood (2). Several at tempts (7,8,6,4,3) have been made to improve  the technique for preparation and photograph ing of perineal patterns of Meloidogyne spp.  Most of the cases cuticular patterns are photo graphed to record the morphological charac ters therein and stored for a short period and  later disposed off. However, preservation of  the patterns for subsequent study is much not  known to those working with routine identifica tion of Meloidogyne spp. In fact, the patterns on  the Meloidogyne spp. female perineum disappear  with the time due to dehydration and decaying of  adhering body tissues.
Keywords: aluminium; glycerine mounted; Meloidogyne